Innovation and Human Resource Development: A Case Study in South Sulawesi - Imbaruddin, Amir; Chairunisa, Frida; Asmarianti, Asmarianti (KnE Social Sciences, 2022)
Human resources is a key factor of an innovative organization. The literature generally states that innovation in public organizations is largely determined by the quality of their human resources. The purpose of this study was to determine how innovation in a government organization can improve the competence of its human resources. This research was conducted on ten public service innovations introduced by the Government of Bone Regency, South Sulawesi. A qualitative approach was used with a case study. Data on these ten public service innovations were collected through focus group discussions and in-depth interviews with innovators. This study found that increasing the competence of human resources in organizations that implement innovations can occur through a range of factors: top management support; rewards; staff diversity; involvement of every member of the organization; experiments; and teamwork. Keywords: innovation, public service, human resource development